Partisan differences in healthcare decision-making: Evidence from a vaccine experiment - Brandyn F. Churchill; Xiaoxue Sherry Gao; Rong Rong (PLoS ONE, 2026)
Policymakers use information campaigns to alter health behaviors, but their effectiveness depends on how the information compares to viewers’ initial beliefs and their perceptions of its value. In August 2024, we experimentally tested whether political identity influenced how individuals responded to information about the COVID-19 vaccine. Our sample included 288 self-identified Democrats and 291 self-identified Republicans. We found that Democrats and Republicans similarly overestimated the frequency and severity of COVID-19 infections, as well as the vaccination rate. Participants were not better at predicting the COVID-19 experiences of their concordant party. However, participants who learned they underestimated the discordant party vaccination rate were more likely to report an intent to receive a COVID-19 vaccine.